Implementation of Application for Ownership of State Land in Comparable Railroad Tracks - Andrian Shidiq; Sri Endah Wahyuningsih; Ngadino Ngadino (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study is to 1) Know the implementation of land rights applications that are located along the railroad tracks in Pucangsawit Village, Surakarta City. 2) Knowing the obstacles that arise in the implementation of applications for land rights located on the equivalent of railroad tracks in the Pucangsawit Village, Surakarta City. The data used in this research are primary data, secondary data, and tertiary data that can support this study, which are then analyzed using descriptive analytical methods.Based on the results of data analysis, it is concluded that: 1) there is a desire of the community around the equivalent of the railroad tracks in Pucangsawit Village, Surakarta City to have a Freehold certificate. The land he occupies is state land which is beyond the control of PT. KAI Daop Jogjakarta in accordance with the technical recommendations issued by PT. KAI daop Jogjakarta. The basis for the consideration of granting a property certificate from the Surakarta City Land Office is that the community members who apply have controlled and occupied the land for more than 20 years and the land requested is outside the railroad equivalent line whose control is at PT. KAI is in accordance with the recommendation of PT. KAI Daop Jogjakarta. 2) The obstacles faced include, among others, there are still many people along the railroad who do not know the boundaries of land under the control of PT. KAI, the lack of insight and understanding of community members around the railroads regarding land law, especially in filing applications for state land ownership so it needs socialization from related agencies, and there are still complicated procedures and bureaucracy in applying for equivalent state land ownership. railrood tracks that need to be simplifed.